Personality Inventory for DSM-5 (PID-5): cross-cultural adaptation and content validity in the Brazilian context - Barchi-ferreira, Ana Maria; Loureiro, Sonia Regina; Torres, Albina Rodrigues; Da Silva, Thiago Dornela Apolinário; Moreno, André Luiz; Desousa, Diogo Araújo; Chagas, Marcos Hortes Nisihara; Dos Santos, Rafael Guimarães; Machado-de-souza, João Paulo; Chagas, Natália Mota De Sousa; Hallak, Jaime Eduardo C.; Crippa, José Alexandre De Souza; et al. (Associação de Psiquiatria do Rio Grande do Sul, 2019)
AbstractObjectiveTo describe the process of cross-cultural adaptation of the Personality Inventory for DSM-5 (PID-5) to the Brazilian context.MethodCross-cultural adaptation involved the steps of independent translation of the instrument, synthesis version, and back-translation. Analysis of content validity was conducted by a multidisciplinary expert committee and consisted of quantitative assessment of agreement indicators. The test was then applied to a target population.ResultAll the steps required for a cross-cultural adaptation were followed and satisfactory agreement values (≥ 4.75) were reached for most of the structures assessed. Most of the changes suggested by the experts were followed; these changes consisted primarily of adjustments to verb tense and agreement and the inclusion of letters and words to allow gender inflection. In the pre-test, no suggestions were made and the instrument was considered comprehensible.ConclusionThe Brazilian version of the PID-5 was found to be adequate to the Brazilian context from semantic, idiomatic, cultural, and conceptual perspectives. The Brazilian version assessed here can be freely used, was approved by the publishers who hold the copyright on the instrument, and is considered the official version of the instrument. New studies are underway to determine the validity and reliability of the PID-5.

ResumoObjetivoApresentar o processo de adaptação transcultural do Personality Inventory for DSM-5 (PID-5) para o contexto brasileiro.MétodoA adaptação transcultural envolveu as etapas de tradução independente, versão síntese e retrotradução. A validade de conteúdo foi realizada por um comitê multidisciplinar de especialistas, com avaliação quantitativa dos índices de concordância. Por fim, o pré-teste foi conduzido com a população-alvo.ResultadoTodos os estágios da adaptação transcultural foram seguidos, e na maioria das estruturas avaliadas, os valores de concordância foram satisfatórios (≥ 4.75). Grande parte das sugestões de modificações feitas pelos especialistas foram acatadas, sendo as principais relacionadas a ajustes no tempo e concordância verbal e a inclusão de letras e palavras para permitir a flexão de gênero. No pré-teste nenhuma sugestão foi apresentada e o instrumento foi considerado compreensível.ConclusãoA versão brasileira do PID-5 mostrou-se adequada ao contexto brasileiro sob as perspectivas semântica, idiomática, cultural e conceitual. A versão brasileira avaliada é de uso livre, foi aprovada pelas editoras responsáveis pelos direitos autorais do instrumento e é considerada oficial. Novos estudos estão sendo conduzidos para aprimorar a busca por evidencias de validade e confiabilidade.
Inventário de Personalidade para o DSM-5 (PID-5): adaptação transcultural e validade de conteúdo para o contexto brasileiro
Keywords: Personality; scale; cross-cultural adaptation; content validity; PID-5; Personalidade; escalas; adaptação transcultural; validade de conteúdo; PID-5